Mathematical Approach with Optimal Control: Reduction of Unemployment Problem in Bangladesh - Mallick, Uzzwal Kumar; Biswas, Md. Haider Ali (Journal of Applied Nonlinear Dynamics, 2026)
Unemployment problems have become the most immense concerns all over the world. This issue is significantly an alarming concern in Bangladesh as well. This paper deals with a nonlinear mathematical model of unemployment which describes the situation of unemployment, employment and vacancies. The system of nonlinear differential equations has been developed and analyzed with two policies of government. In this study, we describe and analyze the modified model and check the stability of equilibrium points of the model. We also discuss the characteristics of states at equilibrium point for various parameters. Specially, we establish a project of five years toreduce the unemployment problems. We also simulate our model in the present of two optimal controls of unemployment model using optimal control technique.